Winter wind storms - Kruschke, Tim (2015)
Wind storms globally pose the most important natural hazard from a socio- economic perspective. For the European continent, it is especially winter storms related to synopticscale extra-tropical cyclones that often affect several countries at the same time bearing high risk of cumulative loss. Societal and economic stakeholders are interested in different aspects regarding these phenomena. On the one hand, (re-)insurance loss modeling requires high spatio-temporal resolution information for winter storms that happened in the past as well as physically consistent scenarios of storm events that could happen. On the other hand, socio-economic planning activities would benefit from any reliable information regarding the frequency of damage-prone storm events for the upcoming seasons and years. The current thesis addresses three aspects in this context: (i) It further develops an objective impact-oriented identification scheme regarding such wind storms. (ii) State-of- the-art decadal climate forecasts are analyzed whether they can provide skillful predictions of Northern Hemisphere winter storm frequency. (iii) A statistical downscaling approach is developed, efficiently estimating high resolution surface gusts from coarse reanalysis and model data. All three topics are successfully tackled. The objective identification procedure is advanced in several aspects, including a more sophisticated spatio-temporal tracking of identified storms. The actual revision of the scheme is applied to the ERA-Interim-reanalysis, yielding the first consistent global climatology of recent wind storm climate. In this context, it is shown that the algorithm is also suitable for other than its core target, that is extra-tropical winter storms. Properties of different storm types are compared, revealing several interesting facts. An exemplary result is the systematically higher translation velocity related to greater travel distances of winter storms over the North Pacific when compared to the North Atlantic, resulting into higher storm ...